Dentinogénesis imperfecta asociada a osteogénesis imperfecta Tipo I de Shields - Soto Llanos, Libia; Marín, Paloma (Revista Estomatología, 2000)
The authors reviewed literature re1ated to dental abnormalities associated with osteogenesis imperfecta. This abnormality named, Dentinogenesis imperfecta type 1 of Shie1ds or opalescent dentin, was found in a 4 years old girl, who consulted the Child and Adolescent' s clinic, in the dental school ofthe Valle University. She was remihed by her pediatrician and the concem of her parents for the abnormal color present in her teeth.